New distributional records and natural history data of Vates phoenix Rivera et al., 2020 (Mantodea: Mantidae) - Gabriel de A. P. Gomes; Leonardo M. Lanna; Luiz C. Pinho (Entomological Communications, 2024)
Vates phoenix Rivera et al., 2020 (Mantodea: Mantidae) is endemic to the Atlantic Rainforest of Brazil, known to the states of Rio de Janeiro and São Paulo. Integrating field collection and records from iNaturalist, the species’ distribution is extended further south, west and north, with confirmed new occurrences to the states of Paraná, Santa Catarina, Minas Gerais, Espírito Santo, and Bahia. The observations provide insights into the species’ natural history and the importance of combining multiple data sources, including citizen science, to provide greater information on elusive species.